Decreased S100A9 Expression Promoted Rat Airway Smooth Muscle Cell Proliferation by Stimulating ROS Generation and Inhibiting p38 MAPK - Lei-Miao Yin; Xiao-Jie Han; Ting-Ting Duan; Yu-Dong Xu; Yu Wang; Luis Ulloa; Yong-Qing Yang (Canadian Respiratory Journal)
Background. Asthma is a disease with a core abnormality in airway smooth muscle function, and the proliferation of airway smooth muscle cells (ASMCs) plays a pivotal role in asthma airway remodeling. Our previous study showed that S100A9 (S100 calcium-binding protein A9; 400 and 800 ng/mL) significantly inhibited rat ASMCs proliferation at 48 h, and 50–800 ng/mL S100A9 (50, 100, 200, 400, and 800 ng/mL) also induced a lasting effect by significantly inhibiting rat ASMCs proliferation at 72 h in a dose-dependent manner. However, the intracellular effects of S100A9 on ASMCs proliferation remain unknown. Methods. Rat ASMCs with stable S100A9 knockdown were generated using short hairpin RNA. The effects of decreased S100A9 expression on cellular proliferation, the production of reactive oxygen species (ROS), and p38 MAPK pathway protein expression were examined. Results. Decreased intracellular S100A9 expression significantly promoted platelet-derived growth factor-induced rat ASMCs proliferation and increased ROS production. The antioxidative agent N-acetylcysteine significantly inhibited rat ASMCs proliferation. Western blot results showed that the decreased intracellular S100A9 expression significantly inhibited p38 MAPK phosphorylation. Conclusion. Decreased S100A9 expression promoted rat ASMCs proliferation by stimulating ROS generation and inhibiting p38 MAPK. Our study may provide novel insights into the regulation of asthma airway remodeling.